Translation strategies applied by Ulis students when translating idioms from English into Vietnamese: a comparative study = Nghiên cứu so sánh về chiến lược dịch thành ngữ từ tiếng Anh sang tiếng Việt của sinh viên ĐHNN - Lê, Quỳnh Mai (2020)
In the field of translation and interpreting, dealing with cultural elements, especially idioms, is usually one of the most challenging tasks. Apparently, translating idioms while maintaining the nuances of meanings and implicities require a lot of knowledge and skills. This paper examined the translation strategies used by students majoring in translation and interpreting from the University of Languages and International Studies (ULIS) - Vietnam National University (VNU) when encountering English idioms. The data were collected from two groups of students at ULIS through the use of survey questionnaires, and later translation strategies used by two groups of students were compared and contrasted to highlight similarities and differences. The findings shown that both groups utilized four translation strategies for translating English idioms. However, the difference was most significant in pure idioms as the findings indicated that paraphrase was the most favored among senior students for its flexibility while the second-year participants preferred idiom to idiom translation and literal translation